Values as a mediational system for self-construction : contributions from cultural constructivim - Rengifo-Herrera, Francisco José (2014)
The text provides the reader with some theoretical reflections on hu man values in their relationship to self development from a cultural constructivist perspective. We emphasize that the concept of self has theoretical aspects that need to be explored to advance alternative explanations about values. Our perspective emphasizes the dynamics of duality and inclusive separation of psychological processes taking place between subject and culture, as well as the role of semiotic systems in the emergence, organization, and development of values We will address the development of self, here conceived as dialogical self, as well as how constructive and non-constructive values can enable us to better understand the emergence and role of emotions in human development. Finally, the analysis of certain biographical aspects of a former Colombian guerrilla illustrates and highlights the main concepts discussed throughout the text.